Development of a post-synthetic method for tuning the Al content of OSDA-free Beta as a catalyst for conversion of methanol to olefins. Issue 3 (15th September 2015) - Otomo, Ryoichi; Müller, Ulrich; Feyen, Mathias; Yilmaz, Bilge; Meng, Xiangju; Xiao, Feng-Shou; Gies, Hermann; Bao, Xinhe; Zhang, Weiping; De Vos, Dirk; Yokoi, Toshiyuki
Abstract : Post-synthetic modification was performed upon an Al-rich OSDA-free Beta to obtain high-silica Beta catalysts for MTO reaction, achieving a high selectivity to light olefins and long catalyst life. Abstract : Zeolites synthesized without any organic structure-directing agent (OSDA) have several advantages over conventional zeolites synthesized with OSDAs. Their Al-rich compositions, however, are sometimes not suitable for applications as catalysts. In the present study, post-synthetic modification was performed using an Al-rich Beta zeolite synthesized without any OSDAs (designated as "Beta(OF)") to obtain high-silica Beta zeolites. We have successfully developed a facile post-synthetic method for tuning the Al content of Beta(OF) with the * BEA -type structure retained by calcination at >750 °C followed by acid treatment. Solid-state 29 Si and 27 Al MAS NMR analyses revealed that during calcination, framework Al atoms were isomorphously substituted with Si atoms to form high-silica frameworks and concomitant extra-framework Al species. The stability of the obtained frameworks against acid treatment was evaluated in terms of the framework Al content, finding that the framework with the Si/Al ratio higher than 12 is well stabilized enough for acid treatment. Thus, dealuminated Beta(OF) zeolites with high-silica compositions were found to be effective catalysts for the methanol-to-olefin (MTO) reaction; particularly, the Beta zeolite with the Si/Al ratio of 112 maintained the conversion of methanol over 90% with selectivity to C2 –C4 olefins over 70% even at 40 hours on stream at WHSV = 3.2 h −1 .